Análise de indicadores educacionais censitários da política de inclusão escolar : uma proposta metodológica - Santos, Vivian (Universidade Federal de São Carlos, 2017)
The results of the current educational policy destined to promote scholar access to the Special Educational Target Audience (SETA) needs to be analyzed. A possible way of doing this is through census scholar data. However, considering the inconsistencies and difficulties of using these data, so, a question has been risen: how to advance in analysis procedures of the census scholar data aiming to optimize the use of these data to evaluate educational policies? Looking for an answer to this question, this study has as general objective: to explore the limits and possibilities of alternative methodological procedures to analyze census data aiming to optimize the use of these data to evaluate the scholar inclusion policy. And, as specific objectives: 1) to identify and analyze some of the possible inconsistences that are in the enrolment micro data of the census scholar data; 2) to compare the characteristics of basic education students that are SETA to those who are not SETA; 3) To analyze, in a comparing way, the age-grade distortion in basic education of students that are SETA and also those who are not SETA. About the methodology, this is a documental, quantitative and comparative study. The data source is the enrolment microdata of the census scholar data, between 2008 and 2014. The sample is composed of 48 cities located in São Paulo State, three of which are administrative region of this state. The results of these cities were combined. To read, treat and analyze the data, the statistical softwares IBM SPSS Statistics and Statistical Analysis System were used. To answer the first specific objective, the researcher elaborated counters through the software SAS. To answer the second specific objective, perceptual maps stem from Multiple Correspondence Analysis (MCA) was elaborated, and, for the third specific objective, graphs and sheets were elaborated. The results were organized in three groups, one for each specific objective. The results about the inconsistences showed that it is necessary to improve the census scholar data, specially the register of the students with multiple disabilities. The MCA results showed similarities between the students that are SETA and those who are not SETA, emphasizing the relation that showed more school evasion for male students and, also, a strong relation between students going to kindergarten and reaching high school. In regard to the age-grade diction, the results showed huge rates of students who are SETA, these rates being a lot superior to the students who are not SETA, which demonstrates that SETA students start their regular education later than other students. In conclusion, once comprehended that the objectives were reached, and that this study brings academic and social contributions, since it proposes to advance the analysis field of the subjected studied, and, with these analysis, will make it possible to look to improve the census scholar data, including the treatment of these data, thus improving this statistical tool that is utilized to create and evaluate educational policies in Brazil.
Analysis of census scholar educational indicators of the scholar inclusion policy : a methodological proposal
Keywords: Educação especial; Política de inclusão escolar; Censo escolar; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO